Peran Balai Latihan Kerja Padang dalam Pemberdayaan Perempuan Muslimah di Kota Padang - Budi Harahap, Aisyah (Jurnal at-Taghyir, 2019)
Padang Work Training Center (BLK) is an institution under the auspices of the Indonesian Ministry of Manpower authorized in the field of women's empowerment through apparel garment skills programs. This institution aims to increase or increase knowledge, skills, attitude and work experience for training participants in the field of sewing clothes. This institution empowers women, especially in the city of Padang to be able to be independent in the economic field. BLK Padang Institute educated training participants in 2017 totaling 94 people, and in 2016 there were 95 people consisting of housewives and unemployed women to be trained by experienced instructors. This training runs for 40 working days, and plus training participants must take part in an internship at a garment company for 1 month. It is expected that after receiving training, participants will be able to be independent and can open their own jobs. This training aims to find out the role of Padang BLK in empowering women through the apparel garment skills program, the economic impact after receiving apparel garment training, as well as supporting and inhibiting factors in the apparel garment skills program by Padang BLK. The research method used is in the form of qualitative deepening literature. Data obtained from structured interviews, non-participant observation, and documentation. The results of the study note that Padang BLK empowers women in the form of soft skills and hard skills. Soft skills and hard skills are two things that complement each other in achieving one's aspirations and life goals for trainees. Both are equally important and should be owned by everyone if you want to achieve a success in life. The results of the study note that the training participants succeeded in increasing family income. It was evident from the interview that the trainees could help with the cost of college education from the proceeds of sewing wages. The results of the study also note that there are still many trainees who are not yet independent after receiving apparel garment training, this is due to the absence of business partners from BLK Padang.